1979
DOI: 10.1097/00043764-197902000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Poisoning

Abstract: Chlorhexidine for irrigation of vas: a clinical trial and the study of viability of non-mobile sperms in postvasectomy patients with trypan blue uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0
3

Year Published

1981
1981
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 0 publications
1
89
0
3
Order By: Relevance
“…The occupational effects of hydrogen sulfide poisoning among cesspit and privy cleaners were first discussed by the Italian physician Bernardo Ramazzini in his treatise De morbis artificum diatribe in 1700, translated into English in 1705 [1]. Hydrogen sulfide toxicity became a public health concern in 1777 after several deaths were attributed to the Parisian sewer system.…”
Section: What Is the Historical And Current Epidemiology Of H 2 S Poimentioning
confidence: 99%
See 4 more Smart Citations
“…The occupational effects of hydrogen sulfide poisoning among cesspit and privy cleaners were first discussed by the Italian physician Bernardo Ramazzini in his treatise De morbis artificum diatribe in 1700, translated into English in 1705 [1]. Hydrogen sulfide toxicity became a public health concern in 1777 after several deaths were attributed to the Parisian sewer system.…”
Section: What Is the Historical And Current Epidemiology Of H 2 S Poimentioning
confidence: 99%
“…Through animal studies in the first decade of the 19th century, Dupuytren identified hydrogen sulfide as the substance of the Paris sewer deaths. Despite two separate commissions appointed to investigate the conditions of the Paris sewer systems in 1785 and 1829, deplorable conditions existed with continued off-gassing resulting in reported deaths in 1836 [1,2]. Victor Hugo described these toxic conditions in Les Miserables in 1862: "Slow asphyxia by uncleanliness, a sarcophagus where asphyxia opens its claws in the filth and clutches you by the throat; fetidness mingled with the death-rattle, mud instead of the sand, sulphuretted hydrogen in lieu of the hurricane, ordure instead of the ocean" [3].…”
Section: What Is the Historical And Current Epidemiology Of H 2 S Poimentioning
confidence: 99%
See 3 more Smart Citations